Suicidal ideation estimated with the Plutchik Suicide Risk Scale among resident physicians from two health institutions in Ciudad Obregon, Sonora, Mexico - Lugo Machado, Juan Antonio (2023)
Objective: To evaluate the incidence and factors associated with suicidal ideation in a sample of resident physicians from two institutions. Materials and methods: A descriptive, observational, prospective and cross-sectional study was carried out to estimate the suicidal ideation and associated factors with the Plutchik Suicide Risk Scale among resident physicians from two hospitals between September and October 2022. Descriptive statistics were used with measures of central tendency and dispersion, as well as relative and absolute frequencies. In addition, Pearson’s chi-square goodness of fit test and Kruskal-Wallis H test were used to examine the differences between specialties, and Tukey’s Honest Significant Difference test to determine which specialty was different. Results: A total of 225 surveys were answered, out of which 20 were eliminated due to inadequate completion, leaving 205 complete surveys for analysis. The average age was 28.66 years (SD ± 2.360) and 71.2 % were females. Concerning the specialties, pediatrics was found in 28.8 % of the respondents and anesthesiology in 20.5 %. A significant association between specialties with a value of p = 0.0000 and academic degrees with p = 0.003 (p ≤ 0.05) was evidenced. Differences regarding suicidal ideation were found by specialty: Kruskal-Wallis H test showed a value of p = 0.000 and Tukey’s Honest Significant Difference test revealed that the specialty of gynecology was the different one.Conclusions: According to the results of the study sample, approximately one fourth of the resident physicians had suicidal ideation. Its prevalence in this sample showed no significant difference with respect to its incidence in Latin America. An association between suicidal ideation, medical specialties and academic degree was found. As for the comparison between specialties, gynecology was the one with the highest suicidal ideation rate. This work had some limitations; for example, the groups were very heterogeneous, a probabilistic selection technique was not used, and the statistical tests were nonparametric.